The use and abuse of forced migration and displacement as a weapon of war - Simeon, James C. (Frontiers in Human Dynamics, 2023)
It is undeniable that forced migration and displacement is a “weapon of war.” To understand the ever-escalating refugee crisis in the world today and how it might be addressed, it is necessary to examine its “root cause(s).” Organized political violence in the form of either war or protracted armed conflict or oppressive dictatorial authoritarianism or totalitarianism are the prime drivers of forced migration and displacement in the world today. The most recent statistics on the world's forcibly displaced demonstrates their direct correlation to war and protracted armed conflict. The vast bulk of the world's forcibly displaced come from war torn countries. What is too often ignored in the academic literature on refugees and forced migration is that civilian non-combatants are often used as “weapons of war.” Mary Kaldor's “new wars” thesis is premised on the notion that wars and protracted armed conflicts defy solution because it is in the interest of the opposing combatants to continue the fighting, consequently, wars are characterized as “endless.” This has obvious implications for the continuous increase in the number of forced migrants in the world today. And, further, the “new wars” thesis postulates that civilian non-combatants are deliberately targeted during protracted armed conflicts or wars. Kelly Greenhill has presented evidence that “coercive engineered migration” is utilized to a State's advantage over another State. The weaponization of civilian non-combatants is a trigger for mass forced migration. Three recent cases dealing with genocide are offered as illustrations: Bosnia; Rwanda; and the Syria Civil War, with the Sieges at Homs and Aleppo. The article concludes with the consideration of the “endless cycle of war” that includes forced migration, smuggling, human trafficking, and other international crimes such as dealing in drugs and arms. All these elements are inter-connected and feed off each other and to be able to break this “endless cycle of war,” there must be a concerted and simultaneous effort to address all these things together. Only by doing so can we ever hope to achieve a “sustainable peace” and thereby end the use and abuse of forced migration and displacement as a “weapon of war.”